Analysis of Unbearable Pressures on The Great Barrier Reef Ecosystem - Wang, Motong (Transactions on Environment, Energy and Earth Sciences, 2024)
Under the trend of global warming, coral reef ecosystems are under stress beyond the scope of the system to repair itself. The Great Barrier Reef (GBR) ecosystem, as the most representative coral reef ecosystem, is facing difficulties such as coral bleaching and reduced coral abundance due to excessive stressors. Based on the existing scientific research results and relevant experimental data, the existing stressors and their consequent impacts in the GBR ecosystem were reviewed. At present, the coral reef ecosystem in the GBR can be surveyed and clearly affected by three human-induced stressors: water quality, overfishing, and climate change. Water pollution from agriculture, industry and tourism surrounding the GBR ecosystem has led to a decrease in the ecosystem's energy supply and an increase in the prevalence of Marine life. Overfishing has resulted in the removal of vital roles that maintain the GBR ecosystem from the GBR ecosystem, limiting the productivity of the reef ecosystem. Climate change is hitting calcium-dependent Marine life in the GBR ecosystem and reducing the reproductive success of Marine life. The better understanding of the stressors coral reef ecosystems is facing can help us in our efforts to protect coral reef ecosystems in the future and help the organisms in the coral reef ecosystems adapting environmental changes brought by global warming, while bring down the influence of human activities on the ecosystem through policies.